Dissecting Cellulitis of the Scalp Successfully Treated with a Combination of Ixekizumab and Tofacitinib - Qiu M; Man X; Jing J (Journal of Inflammation Research)
Miaoqi Qiu, Xiaoyong Man, Jing Jing Department of Dermatology, Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of ChinaCorrespondence: Jing Jing, Department of Dermatology, Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China, 88th Jiefang Road, Tel +86-13758189389, Email haitong1987@163.comAim: Dissecting Cellulitis of the Scalp (DCS) is a rare form of neutrophilic primary cicatricial alopecia (PCA). It usually occurs in black males and is less commonly reported in Asian populations. There are no systematic treatment guidelines for this disease, the hypothetical co-pathogenesis of DCS and hidradenitis suppurativa (HS) has led to the fact that most of the current biological therapies for DCS are based on the experience of HS, such as biologics and JAK inhibitors. Both agents alone have been reported in the treatment of HS and DCS, but the efficacy is uncertain. For severely refractory DCS, the combination of biologics and Janus kinase inhibitors (JAKi) may be a new strategy. In this case, we describe a 28-year-old Chinese young man with a confirmed diagnosis of severe DCS who experienced nodules resolve and hair regrowth after a combination use of ixekizumab and tofacitinib. This is the first case of DCS treated with a combination of IL-17 inhibitors and JAKi.Purpose: We hope that dermatologists should be aware that early diagnosis of DCS and the application of biologics are essential to quickly control symptoms and prevent from PCA and keloids.Patients and Methods: This is a patient from the Department of Dermatology, the Second Affiliated Hospital of Zhejiang University School of Medicine.Keywords: dissecting cellulitis of the scalp, primary cicatricial alopecia, treatment, ixekizumab, tofacitinib